Significance of RNA N6-methyladenosine regulators in the diagnosis and subtype classification of coronary heart disease using the Gene Expression Omnibus database - Jiang, Yu; Pan, Yaqiang; Long, Tao; Qi, Junqing; Liu, Jianchao; Zhang, Mengya (Frontiers in Cardiovascular Medicine, 2023)
Many investigations have revealed that alterations in m6A modification levels may be linked to coronary heart disease (CHD). m6A alterations are strongly associated with the etiology of cardiovascular disease, including functions in cardiovascular gene expression regulation, cell signaling, apoptosis, and autophagy. However, the specific link between m6A alteration and CHD warrants further investigation. In this research, 37 important m6A regulators were identified by comparing non-CHD and CHD patients from the GSE20680, GSE20681, and GSE71226 datasets. To predict the risk of CHD, seven candidate m6A regulators (CBLL1, HNRNPC, YTHDC2, YTHDF1, YTHDF2, YTHDF3, ZC3H13) were screened using the logistic regression model. Based on the seven possible m6A regulators, a nomogram model was constructed. An examination of decision curves revealed that CHD patients could benefit from the nomogram model. On the basis of the selected relevant m6A regulators, patients with CHD were separated into two m6A clusters (cluster1 and cluster2) using the consensus clustering approach. The Single Sample Gene Set Enrichment Analysis (ssGSEA) and CIBERSORT methods were used to estimate the immunological characteristics of two separate m6A Gene Clusters; the results indicated a close association between seven candidate genes and immune cell composition. The drug sensitivity of seven candidate regulators was predicted, and these seven regulators appeared in numerous diseases as pharmacological targets while displaying strong drug sensitivity. In conclusion, m6A regulators play crucial roles in the development of CHD. Our research of m6A clusters may facilitate the development of novel molecular therapies and inform future immunotherapeutic methods for CHD.